Economic evaluation of finishing beef cattle at pasture or in feedlot with high grain diet - Filho, Helio José de Araújo; Malafaia, Pedro; de Carvalho, Carlos Augusto Brandão; Garcia, Felipe Zumkeller; de Souza, Vinícius Carneiro [UNESP]; Ferreira, Robson Leandro; Risso, Thainá de Lima (My University, 2019)
This study aimed to evaluate the economic aspects of finishing beef cattle with mineral supplementation at pasture (PSM), protein-energy supplementation (SPE) at pasture and in the feedlot with high grain (AG) diet. Sixty castrated male ½ Nelore x Angus were used in a completely randomized design with twenty animals in each group. Cattle finished in the AG system reached the target slaughter weight earlier and had higher average daily and carcass gain, followed by those of the SPE and PSM groups (p<0.05). The PSM system generated the lowest effective operating cost, total operating cost and total cost. Higher gross and net margins, net results, profitability and simple yields were obtained in the PSM, SPE and AG groups, respectively. However, when the cash flow were corrected by the general price-to-availability index (IGP-DI), the SPE system generated higher results, profitability and rentability, while the lower values of these indicators were from the PSM group. Both feedlot and pasture supplementation based on AG diet might be viable strategies to support the finishing cattle at pasture.
Keywords: Economic evaluation; Feedlot; High grain diet